2002
DOI: 10.1093/heapro/17.1.31
|View full text |Cite
|
Sign up to set email alerts
|

More than words? The status and impact of smoking policies in Scottish schools

Abstract: The aim of this study was to investigate the current status of smoking policies in Scottish schools, and the relationship between policy status, enforcement of smoking restrictions and perceptions of smoking behaviour among pupils and teachers. A representative sample of 15-year-old school pupils from 77 Scottish secondary schools was surveyed in 1998 regarding their perceptions of smoking in several locations within and outside the school building. Two staff members from each school were also surveyed regardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
1
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 17 publications
2
47
1
4
Order By: Relevance
“…However, Wakefield et al [28] in a study of high school students in U.S., showed the existence of a smoking ban in school had little effect on reducing smoking prevalence unless strongly enforced student smoking restriction on school property. A similar result was found in a representative sample of 15-yearold school students, where consistent enforcement of smoking restrictions was associated with significantly lower levels of perceived smoking practices in school [29].…”
Section: The Influence Of School Environmentsupporting
confidence: 82%
See 2 more Smart Citations
“…However, Wakefield et al [28] in a study of high school students in U.S., showed the existence of a smoking ban in school had little effect on reducing smoking prevalence unless strongly enforced student smoking restriction on school property. A similar result was found in a representative sample of 15-yearold school students, where consistent enforcement of smoking restrictions was associated with significantly lower levels of perceived smoking practices in school [29].…”
Section: The Influence Of School Environmentsupporting
confidence: 82%
“…In other words, wide variation exists from school to school in terms of policies development and enforcement in preventing students' cigarette smoking behavior. Previous studies have indicated that schools are more likely to have a ban smoking policy directed at students than staff members [29,31]. It is likely that most of these schools have a policy against students smoking on campus, but may still allow staff and visitors to smoke in a designated area [19], where students would be potentially exposed to the smoking behavior.…”
Section: The Influence Of School Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in the Control of Adolescent Smoking (CAS) Study, a project developed in eight European countries, with the aim of investigating the relationships between national tobacco policies, school smoking policies and adolescent smoking, there are significantly lower prevalence rates in smoke-free schools (Griesbach et al 2002;Wold et al 2004). In order to achieve greater effectiveness, it is widely recognized that a smoking prevention programme should contain the following components (Raczynski and Di Clemente 1997): sustained treatment, characterized by booster sessions over several years (such as considering the intervention as a dose of vaccine to be administered each year for a certain period); reinforcement of the treatment within the community, involving parents and the mass media; and programming smoking prevention activities within a more comprehensive school health promotion programme.…”
Section: Discussionmentioning
confidence: 99%
“…Wie gut die Einhaltung der Rauchverbote überwacht wurde, war die einzige Variable, die bestehende Unterschiede in der Rauchprävalenz zwischen den untersuchten Schulen erklären konnte. Die Kontrolle der Rauchverbote stand auch in Schottland in Zusammenhang mit dem Konsumverhalten der Schüler [11]. An allen Orten, an denen Lehrer regelmäßig Kontrollen durchführ-ten, sah man signifikant weniger rauchende Schüler als an anderen Orten.…”
Section: Durchsetzung Der Regelungen/kontrollenunclassified